‘Emerald Beauty’ and ‘Emerald Sprite’ Cotoneasters - Ryan N. Contreras (HortScience, 2023)
Cotoneaster (Rosaceae) is a large genus of deciduous and evergreen plants that range from prostrate groundcovers to small trees. The genus is separated into two subgenera including Chaenopetalum with white flowers and Cotoneaster with pink flowers. The former includes common cultivars such as Coral Beauty. Cotoneasters are generally utilitarian shrubs used in mass, often as hedge plants. There has been relatively little modern breeding, although there are many available cultivars. Dirr (2009) noted that beyond Dr. John Ruter at University of Georgia, virtually no breeders in the United States are pursuing efforts to improve and introduce cultivars of this utilitarian genus. Primary challenges for breeders to address are weediness of some species (e.g., C. lacteus), poor growth habit, and susceptibility to fire blight caused by Erwinia amylovora (Contreras 2018). Other groups have documented resistance to fire blight among cotoneasters (Davis and Peterson 1976; Lecomte and Cadic 1993; Losing 1992) or performed some breeding and selection (Bellenot-Kapusta et al. 2002; Persiel and Zeller 1981), but fewer studies have been performed in recent decades.